Review of green building demand factors for Malaysia - Aliagha, Godwin Uche (2013)
Green building is redefining building practice and Malaysia is poised for early adoption in recognition of the potential economic and environmental benefits that accrue to it. Available reports tend towards the fact that there will be increase in demand for green buildings with the growth in environmental awareness and increase in corporate social responsibility among the companies as well as growing body of evidence demonstrating that green buildings make financial sense. Despite the growing interest, risks of uncertainties still cloud investment in green building. This paper examines Malaysia efforts to spure green building investment and demand with particlualr focus on Green Building Index (GBI) and the enabling green tax incentives. Subsequently the paper reviews potential factors that enhance green building in Malaysia as well as the underlying challenges and barriers. Based on the review, we can infer that the Malaysia green tax incentives for obtaining GBI certification are significant but not outstanding. They are inherent with notable criticisms and may not be sufficiently attractive to potential real estate investors. The review also empower us to hypothesize that the model of green building demand for Malaysia will comprise seven interrelated factors vis-a-avis:- quest for environmental sustainability, quest for increased productivity, quest for improved internal building conditions, quest for higher building value, quest for cost savings, quest for lower risks, and quest for branding and prestige. And that the nature and strength of relationship among the factors will be moderated by some of the challenges and barriers identified in the review. The paper will be useful to researches, practitioners and policy makers in real estate development and market seeking explanations for factors that could enhace demand for green building in Malaysia.